1989
DOI: 10.1126/science.2543073
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Regulation of a Chloride Current in Heart

Abstract: In isolated heart cells, beta-adrenergic receptor stimulation induced a background current that was suppressed by simultaneous muscarinic receptor stimulation. Direct activation of adenylate cyclase with forskolin also elicited this current, suggesting regulation by adenosine 3',5'-monophosphate (cAMP). This current could be recorded when sodium, calcium, and potassium currents were eliminated by channel antagonists or by ion substitution. Alteration of the chloride equilibrium potential produced changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
166
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(185 citation statements)
references
References 37 publications
18
166
0
1
Order By: Relevance
“…For example it appears that DIDs does not inhibit the adenosine 3':5'-cyclic monophosphate (cyclic AMP)-mediated chloride current in cystic fibrosis airway epithelia (Anderson & Welsh, 1991). In cardiac myocytes, 100gM SITS and DIDS actually enhanced the isoprenaline-induced chloride current which is also mediated by cyclic AMP (Harvey, 1993) although this conductance is sensitive to A-9-C (Harvey & Hume, 1989). In contrast, the voltage-gated chloride conductance in rat cultured astrocytes is significantly inhibited by low concentrations of DIDS (20 f.M) but is insensitive to A-9-C (Gray & Ritchie, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…For example it appears that DIDs does not inhibit the adenosine 3':5'-cyclic monophosphate (cyclic AMP)-mediated chloride current in cystic fibrosis airway epithelia (Anderson & Welsh, 1991). In cardiac myocytes, 100gM SITS and DIDS actually enhanced the isoprenaline-induced chloride current which is also mediated by cyclic AMP (Harvey, 1993) although this conductance is sensitive to A-9-C (Harvey & Hume, 1989). In contrast, the voltage-gated chloride conductance in rat cultured astrocytes is significantly inhibited by low concentrations of DIDS (20 f.M) but is insensitive to A-9-C (Gray & Ritchie, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The role of anions in cardiac electrophysiology received far less attention as physiological and pharmacological research has focused mainly on cation channels [1] until the discovery of the cAMPactivated Cl − current [2,3]. Anion currents are still less understood regarding their molecular identity, physiological role and biophysical, pharmacological properties [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the myocardium, ~-adrenergic agonists regulate a variety of ionic currents (for reviews, see Hartzell, 1988;Gadsby, 1990), including a CI-current identified recently in guinea pig and rabbit ventricular myocytes (Harvey and Hume, 1989;Bahinski, Nairn, Greengard, and Gadsby, 1989b;Matsuoka, Ehara, and Noma, 1990). Activation of that CI-conductance requires phosphorylation by cAMP-dependent protein kinase (PKA) because the CI-conductance can be elicited by direct intracellular application of either cAMP or the catalytic subunit of PKA (Bahinski et al, 1989b), and it can be abolished (Bahinski, Gadsby, Greengard, and Nairn, 1989a;Hwang, Horie, Nairn, and Gadsby, 1992c) by intracellular application of a specific peptide inhibitor of PKA (PKI; i.e., Walsh inhibitor, 5-24-amide; Cheng, Kemp, Pearson, Smith, Misconi, Van Patten, and Walsh, 1986).…”
Section: Introductionmentioning
confidence: 99%